Supervisi Klinis Berbasis Teknologi Informasi di SDIT Permata Mulia Mojokerto - Lailie, Noor; Khamidi, Amrozi; Amalia, Kania; Haq, Mohammad Syahidul (Media Manajemen Pendidikan, 2025)
This Research & Development research aims to develop and test the effectiveness of an Information Technology-based clinical supervision system to improve the quality of teacher supervision and learning at SDIT Permata Mulia. Using the Borg & Gall R&D method, the research includes needs analysis, product development, and trials and evaluations. The results show that the developed system is valid and practical. The implementation of this system is also significantly effective in improving teacher perceptions of supervision transparency (p < 0.001) and contributes to improving the quality of learning (substantial gain score increase in the experimental group). In conclusion, the IT-based supervision system is an effective innovation for optimizing clinical supervision and teacher professional development.